Occurrence and diagnostic of intermittent shedding of Staphylococcus aureus in bovine mammary infection - Mues, Lena; Kemper, Nicole; Blumenberg, Julia Anna (Frontiers in Veterinary Science, 2025)
Bovine mastitis is a major problem with huge economic losses in dairy farming worldwide. One of the most common pathogens is Staphylococcus aureus, which is highly contagious and often spread during milking. A sanitation of a dairy herd can be challenging particularly in terms of diagnostics, because of intermittent shedding of Staphylococcus aureus in milk. The observation of intermittent shedding of Staphylococcus aureus in longitudinal studies and applied detection methods were reviewed in this study. Categorization of detection methods is used to describe the basic influence of intermittent shedding on sensitivity of diagnostic of each category. The laboratory diagnostic methods evaluated have a wide range regarding the detection limit (40 cfu/mL−106 cfu/mL). A low detection limit is essential for the detection of even chronically infected cows with intermittent shedding of the pathogen. The literature overview shows that only a few studies (n = 6) examined occurrence of intermittent shedding of Staphylococcus aureus in milk at cow level. A detection-free period of ≤ 0.5–1 d was only observed in 3 studies.